(untitled) (Journal of Global Accounting, 2024)
This study examined the effect of police trust fund tax on net investment of listed Communication firms in Nigeria for eleven (11) year period spanning from 2012-2022. Panel data were used in this study, which were obtained from the annual reports and accounts of ten (10) listed Communication companies for the periods 2012-2022. Ex-Post Facto research design was employed. Inferential statistics using Pearson correlation coefficient, Panel least square regression analysis and Hausman test were employed to test the hypothesis of the study. Conclusively, the results of the tested hypotheses revealed that Police Trust Fund Tax has a negative and non significant effect on Net Investment (β1 = -1.403370; p-value = 0.1746 > 0.05) of listed Communication firms in Nigeria at 5% level of significance respectively. The study recommended amongst others that Government should implement policies that would provide the critical needs of the Nigeria Police Force and its institutions in order to ensure the overall improvement and efficient discharge of their duties and responsibilities, in order to build a well-trained, equipped and motivated Nigerian Police Force that is Proactive, Prompt and Responsive to security challenges effectively.